Causalities of human wildlife conflict in Kashmir valley, India; a neglected form of trauma: our 10 year study - Moten, Tarseem Lal; Bhat, Towseef Ahmad; Gulzar, Amara; Mir, Ayaz; Mir, Furqaan (International Journal of Research in Medical Sciences, 2017)
Background: Human wild life conflict is increasing at an alarming rate. The topography of Kashmir valley, India makes the people at risk of wild life injuries all the time. We have been seeing increasing number of victims of wild life injuries during harvesting season for many years with maximum number of injuries due to bear maul. Objective was to see the incidence and pattern of injuries due to human wild life conflict besides surgical challenges and outcome of such injuries Methods: This was a retrospective study of 10 years duration done between 2005 to 2016. Data was collected from hospital records and records of wild life conservation department. Results: Human wild life conflict is increasing at an alarming rate. Bear was the most common animal responsible for human animal conflict, followed by leopard. Monkey and red fox attacks were less common and less lethal. Mortality was highest in leopard attacks. Conclusions: Human wild life conflict is certainly increasing. Most of the attacks due to bear and leopard are devastating. Most of the survivors of such attacks are left with some degree of disability and psychiatric disturbances. Maintaining ecological balance is the best way to control human animal conflict.